MRI‐Related Heating of Implants and Devices: A Review - Winter, Lukas; Seifert, Frank; Zilberti, Luca; Murbach, Manuel; Ittermann, Bernd (Journal of magnetic resonance imaging, 2021)
During an MRI scan, the radiofrequency field from the scanner's transmit coil, but also the switched gradient fields, induce currents in any conductive object in the bore. This makes any metallic medical implant an additional risk for an MRI patient, because those currents can heat up the surrounding tissues to dangerous levels. This is one of the reasons why implants are, until today, considered a contraindication for MRI; for example, by scanner manufacturers. Due to the increasing prevalence of medical implants in our aging societies, such general exclusion is no longer acceptable. Also, it should be no longer needed, because of a much‐improved safety‐assessment methodology, in particular in the field of numerical simulations. The present article reviews existing literature on implant‐related heating effects in MRI. Concepts for risk assessment and quantification are presented and also some first attempts towards an active safety management and risk mitigation. Level of Evidence 5 Technical Efficacy Stage 5